2008
DOI: 10.4049/jimmunol.180.6.3655
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Dependence of Plasma Cells and Independence of Memory B Cells on BAFF and APRIL

Abstract: Memory B (BMEM) cells and long-lived bone marrow plasma cells (BM-PCs) persist within local environmental survival niches that afford cellular longevity. However, the factors supporting BMEM cell survival within the secondary lymphoid organs and allowing BM-PC persistence in the bone marrow remain poorly characterized. We report herein that long-lived BMEM cell survival and function are completely independent of BAFF (B cell-activating factor of the TNF family) or APRIL (a proliferation-inducing ligand). Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
410
4
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(438 citation statements)
references
References 18 publications
22
410
4
2
Order By: Relevance
“…Atacicept blocks APRIL in addition to BLyS (8), and APRIL supports plasma cells in the absence of BLyS (34). Therefore, it would be reasonable to hypothesize that the reduction in plasma cell numbers achieved with atacicept, but not belimumab (33), in patients with RA may have additional clinical effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atacicept blocks APRIL in addition to BLyS (8), and APRIL supports plasma cells in the absence of BLyS (34). Therefore, it would be reasonable to hypothesize that the reduction in plasma cell numbers achieved with atacicept, but not belimumab (33), in patients with RA may have additional clinical effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical efficacy associated with decreased levels of both RF and ACPAs has been demonstrated at 6 months after initiation of treatment with the B celltargeting therapy, rituximab, in RA (35,36), suggesting that the 26-week treatment period in our study was of sufficient duration to evaluate clinical benefit. Rituximab (37) and atacicept (34,38) target different B cell populations, and rituximab may interfere with antigen presentation, cytokine production, and the direct stimulation of T cells by B cells, in addition to its effects on autoantibody production (5), all of which may be relevant for its clinical efficacy. Thus, comparing the time course of the effects of rituximab and atacicept may not be informative.…”
Section: Discussionmentioning
confidence: 99%
“…It deserves mentioning that Ag-specific PCs slowly but steadily accumulated in vaccinated APRIL 2/2 mice and that the BM of APRIL 2/2 mice contains normal total PC numbers (E. Belnoue, C. Tougne, and C.-A. Siegrist, unpublished observations) (22), whereas adoptively transferred PC rapidly disappeared (Fig. 3G).…”
Section: Discussionmentioning
confidence: 99%
“…A critical in vivo role of APRIL, but not BAFF, was demonstrated using APRIL 2/2 and BAFF 2/2 mice (11). Conversely, the use of blocking reagents concluded that either APRIL or BAFF could support PC survival (21,22). We reported the role of APRIL-producing BM Gr1 int CD11b + cells in the support of BMPCs, referring to these cells as resident BM monocytes (11).…”
mentioning
confidence: 99%
“…Current views are that BCMA may be important for the survival of some, but not all plasma cells, and that both BAFF and APRIL may contribute to this effect. Blocking either BAFF, or APRIL, independently does not result in differences in numbers of bone marrow plasma cells, but blocking both reduces numbers dramatically (18).…”
Section: Introductionmentioning
confidence: 96%